Ironing out the Details: Exploring the Role of Iron and Heme in Blood-Sucking Arthropods - Whiten, Shavonn R.; Eggleston, Heather; Adelman, Zach N. (Frontiers in Physiology, 2018)
Heme and iron are essential molecules for many physiological processes and yet have the ability to cause oxidative damage such as lipid peroxidation, protein degradation, and ultimately cell death if not controlled. Blood-sucking arthropods have evolved diverse methods to protect themselves against iron/heme-related damage, as the act of blood feeding itself is high risk, high reward process. Protective mechanisms in medically important arthropods include the midgut peritrophic matrix in mosquitoes, heme aggregation into the crystalline structure hemozoin in the kissing bug and hemosomes in ticks. Once heme and iron pass these protective mechanisms they are presumed to enter the midgut epithelial cells via membrane-bound transporters, though relatively few iron or heme transporters have been identified in bloodsucking arthropods. Upon iron entry into midgut epithelial cells, ferritin serves as the universal storage protein and transport for dietary iron in many organisms including arthropods. In addition to its role as a nutrient, heme is also an important signaling molecule in the midgut epithelial cells for many physiological processes including vitellogenesis. This review article will summarize recent advancements in heme/iron uptake, detoxification and exportation in bloodfeeding arthropods. While initial strides have been made at ironing out the role of dietary iron and heme in arthropods, much still remains to be discovered as these molecules may serve as novel targets for the control of many arthropod pests.